Dynamic and thermodynamic characteristics of ocean response to super typhoon Mangkhut in the South China Sea - Wu, Zhiyuan; Zou, Zeyuan; Chen, Jie; Luo, Hongmei; Deng, Bin; Jiang, Changbo; Lv, Zhao; Zhang, Haojian (Frontiers in Marine Science, 2025)
The impact of the South China Sea (SCS) to the super typhoon Mangkhut (2018) and the air-sea interaction are evaluated through COAWST model in this study which fully coupled with the atmosphere model (WRF), the ocean model (ROMS), and the wave model (SWAN). A comparison of our modeled results with several buoys and tide stations revealed remarkable consistency, the minimum root mean square error (RMSE) for wind speed, significant wave height, and water level are 3.013 m/s, 0.641m, 0.007m. During the development and dissipation of super typhoon Mangkhut, the Coriolis force caused the typhoon wind field to exhibit a pronounced rightward deflection. The characteristics of the significant wave height field are generally similar to those of the wind field, although there is a temporal lag of several hours. Moreover, we researched on the spatiotemporal variations of sea surface temperature (SST) impact by the Mangkhut’s passage, and found that it exhibits two main characteristics: spatial asymmetry and temporal lag. The spatial asymmetry is primarily governed by typhoon-generated wind fields, while the temporal lag is mainly controlled by upwelling and vertical mixing processes during the typhoon’s passage, with Ekman pumping playing a pivotal role in these dynamics. This study mainly concentrates on investigating the dynamic and thermodynamic responses of the ocean during extreme weather conditions by using COAWST model.